Growth and Reproduction Performances of Chaugarkha Goat of Kumaon Region of Uttarakhand - Chauhan, Indrasen; Meena, Raj Kumar; Gautam, Siddharth; Kharayat, Nitish Singh; Jana, Chandrakanta; Sankar, Muthu (International Journal of Bio-resource and Stress Management, 2021)
Chaugarkha goats are small size meat purpose breed distributed in temperate Kumaon region of Uttarakhand, India and the breed is identified as a unique new breed since 1992. The breeding tract of Chaugarkha goat is spread across four mountainous districts Almora, Bageshwar, Champawat and Pithoragarh of Kumaon region. The growth performance was analyzed by least squares analysis and information on reproduction parameters of Chaugarkha goats was generated. Least squares means at birth, three months, six months, nine months and twelve months were 1.83±0.03, 7.67±0.13, 11.45±0.17, 14.89±0.27 and 18.98±0.26 kg, respectively. Age at first mating (days), age at first kidding (days), kidding interval (days), service period (days) and gestation period (days) were 439.65±23.93, 583.83±32.66, 267.46±10.23, 204.30±17.57, and 148.98±0.70, respectively. The litter size was 1.23±0.04. Oestrous cycle length (days) and estrus duration (hrs) were 21.31±0.32, and 52.0±1.36, respectively. In the cluster 4 higher performances were recorded and it was carried forward from three months through six and nine months upto twelve months. But, no definite trend was observed for the effects of year. The male had higher estimates than females at all ages, which is along the expected line. The generated reproduction parameters will be helpful in the formulation and implementation of breeding plans.